The Problem of Labour Migration of Ukrainian Peasants and Burghers in the Internal Policy of Russian Empire in the Second Half of the Nineteenth – Early Twentieth Centuries - Yakymenko, M.; Sharavara, T.; Makarets, S.; Nikolaienko, Yu. (Український історичний журнал, 2019)
The purpose of this research is to highlight the results of Russian
policy for Ukrainian labour migrants, which is both of theoretical and practical
importance, since it enables modern Ukrainian leaders to take into account positive
and negative experience of unprivileged classes labour migration in the late 19th and
in the early 20th centuries. The research methods are based on the main principles
of historicist tradition, scientific objectivity, comprehensive approach and data
classification. In order to achieve the purpose the authors use a number of general
scientific methods (analysis, synthesis, classification) as well as specific historical
methods, such as problematic and chronological, comparative, retrospective and
method of periodization. As the result of the research, the authors have made a
conclusion about quite high activity of the inhabitants of Dnipro Ukraine in
migration movements during the second half of the 19th century and the early of
the 20th century due to the lack of land. The economic reasons were predominant for
most migrants, as they were unable to satisfy their primary needs within their region.
These are general observations. To be more precise, we can determine a certain range
of social and economic factors which made direct and indirect impact on stepping
up of migration movements on Ukrainian lands of the Russian empire within
the period of 1861–1917. These factors include: 1) the lack of land for most small
agrarian producers due to the implementation of legislation acts concerning former
serf (in 1861), udilni (in 1863) and state peasants (in 1866); 2) small labour market
in the late 19th and early 20th century that resulted in agrarian overpopulation of
Ukrainian villages (from 7 to 12 million by various estimates); 3) the availability
of the special social unprivileged class of kozaks who inhabited Left-Bank Ukraine
(with the highest level of migration) and always had a possibility to sell their land
and receive some money to move out; 4) the prevailing government ideas concerning
Ukrainian people as the best colonization element that is proved by a large number
of legislations acts related to so-called "malorosiyski kozaky". Because of fiscal
interests, the central power restricted the intention of some part of its citizens to find
better resources in other regions of the country for a long period. However, the need
for economic growth of remote eastern and south-eastern regions of the empire and
necessity for the defence of these territories from aggressive neighbours, e.g. Japan,
forced the government to provide more possibilities for labour migrants to move from
the densely populated central parts of the country to its borderlands. Мета дослідження полягає у висвітленні наслідків російської політики для українських трудових міґрантів, що має не лише суто теоретичне,
але і практичне значення, адже дозволяє в наш час ураховувати позитивний
та неґативний досвід трудової міґрації непривілейованих станів кінця ХІХ –
початку ХХ ст. Методологія дослідження базується на основних принципах
історизму, наукової об’єктивності, усебічного та системного підходу й систематизації джерел. Використано як загальнонаукові (аналіз, синтез, класифікація), так і спеціальні історичні (проблемно-хронологічний, порівняльно-історичний, періодизації, ретроспективний) методи дослідження. Автори дійшли висновку про досить високу активність мешканців Наддніпрянської
України в міґраційних рухах другої половини ХІХ – початку ХХ ст., спричинену мало- та безземеллям. Загалом визначальними для абсолютної більшості трудових міґрантів були економічні причини, тобто неможливість у межах
свого реґіону задовольнити основні потреби селянсько-міщанської родини. Соціально-економічні фактори, що прямо або побічно впливали на активізацію міґраційних рухів на українських землях Російської імперії в період із 1861 по
1917 рр.: 1) мало- й безземелля основної маси дрібних сільськогосподарських товаровиробників у ході реалізації законодавчих актів щодо колишніх кріпосних (1861 р.), удільних (1863 р.) та державних (1866 р.) селян; 2) вузькість ринку
робочої сили у другій половині ХІХ – на початку ХХ ст., прямим наслідком
чого стало аграрне перенаселення українського села, яке, за різними даними,
охоплювало від 7 до 12 млн осіб; 3) наявність у ґуберніях Лівобережної України, де міґрації були особливо значущими, такої соціальної категорії непривілейованих станів, як козаки, що завжди мали можливість продажу своїх угідь
і, відповідно, отримання для переселення певної суми коштів; 4) панування в
урядових колах думки щодо українців як найкращого колонізаційного елементу, що підтверджується цілою низкою законодавчих актів стосовно поселення так званих «малоросійських козаків». Переслідуючи суто фіскальні мотиви,
центральна влада тривалий час усіляко обмежувала намагання своїх підданих знайти в інших реґіонах країни відповідні засоби життєдіяльності. Проте потреби економічного розвитку східних і південно-східних окраїн імперії,
а також необхідність захисту їх від зазіхань аґресивних сусідів (у тому числі Японії), змушували урядові кола крок за кроком створювати дедалі більші можливості для руху трудових міґрантів із густозаселених центральних реґіонів Росії.